Avaliação da deposição e da agitação de calda em reservatórios de pulverizadores agrícolas utilizando uma análise numérica (CFD) e experimental - Micheli, Gustavo Barbosa [UNESP] (2014)
This paper presents a numerical and experimental study of the behavior of fluid agitation in tanks of agricultural sprayers. Proper agitation of the spray mixture of pesticides in a tank is very important to ensure a uniform spraying throughout the field. The objective of the study was to develop a computermodel capable of predicting tank zones where deposition of pesticides mixture concentrate occurs, and thus aiding in the design of tanks for agricultural sprayers, with cost and time savings. Thus, results of fluid dynamics simulations (CFD) were compared to experimental tests to validate the numerical model. The experimental procedure performed is standardized and consisted on the verification of copper concentration of test solution in three levels of 4000 liters tank, during agitation, re-agitation and tank emptying. Using a single-phase model (water), we assessed the velocity profile and the distribution of shear stress on the tank wall in order to relate these variables to the residue concentration. The comparison between experimental results and the computational model developed indicated that regions with low numerical values of wall shear stress were in agreement with regions of high deposition of copper test solution